Busy Book Media and Vocabulary Mastery: An Experimental Study with Fifth Graders in Rural Area - Amelia Safuf; Rizqi Claudia Wardani.H (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study investigates the effectiveness of educational games in enhancing vocabulary mastery and learning engagement among young English as a Foreign Language (EFL) learners in a rural context. The research was conducted at SD Negeri 14 Kabupaten Sorong over a two-week period and involved eight fifth-grade students, selected through purposive sampling. Employing a pre-experimental design with a one-group pre-test and post-test model, the study aimed to determine whether the use of tactile and interactive educational media—specifically Busy Book games—could significantly improve students’ English vocabulary acquisition and classroom activeness. Data were gathered using vocabulary tests and structured observation checklists, with results analyzed through SPSS version 20 and descriptive percentage analysis. The vocabulary test scores showed a marked improvement, with the average score rising from 32.50 in the pre-test to 81.25 in the post-test. A paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference in students’ vocabulary mastery after the intervention. Observation data also demonstrated a high level of student activeness, with 75% of participants categorized as “very active” during the learning sessions. These findings suggest that the Busy Book, as a low-cost and reusable educational game, is highly effective in fostering vocabulary development and classroom engagement in under-resourced learning environments. Although the study's small sample size limits the generalizability of the results, the outcomes offer valuable insights into the practical application of game-based, multisensory learning tools for improving English instruction at the primary level. The study highlights the potential of contextually appropriate, student-centered strategies for supporting equitable language education in rural Indonesian schools